Escritura creativa en la mejora de las habilidades de redacción en estudiantes del cuarto grado de educación primaria de la institución educativa N° 60589 Saramuro Rio Marañon, Loreto Nauta 2024 - Dorado Castro, Jorge Hernan (2025)
The purpose of the research consisted of: To verify to what extent creative writing enhances writing skills in fourth grade students of the educational institution N°60589 Saramuro río Marañon Loreto Nauta Nauta 2024. Regarding the Problem: To what extent does creative writing enhance students' writing skills? The population consisted of 119 individuals, of which 99 students participated in a quantitative pre-experimental study with pre- and post-tests. Employing the Z-value statistic, estimating the p-value at 0.001 = 0.0%. The null hypothesis is discarded if: p-value is less than 0.05 (p = bilateral asymptotic significance). At a margin of error of 0.001%, creative writing experiences a significant advance. The hypothesis of the study is evidenced at 95% confidence: “Writing skills are significantly enhanced in creative writing with fourth-grade elementary school students.” However, it is crucial to implement constant assessment and feedback systems that make it possible for students to obtain positive feedback on their creative projects. El feedback no solo debe enfocarse en aspectos técnicos de la redacción, sino también en la creatividad y la expresión personal. Organizar actividades fuera del programa académico relacionadas con la producción literaria, como competencias en narración, clubes de escritura y eventos literarios.